A study on epidemiology of foot injuries in South Indian population at a tertiary care centre - Balaji, Gopisankar; Nema, Sandeep; Kumar, Anand (International Journal of Research in Orthopaedics, 2020)
Background: Knowledge of the epidemiology of foot injuries might be useful for implementing injury prevention programmes and for academic research purpose. Methods: This retrospective descriptive study was conducted on patients presenting with foot injuries to our emergency medical service department from May 2018 to April 2019. Results: Total 604 foot injuries were available for final evaluation. There were 461 male and 131 female patients. The mean age was 32.09 years. The commonest mode of injury was road traffic accident. Total 192 feet had only soft tissue injuries while 412 had bony injuries. Total 140 of 323 cases of forefoot injuries were due to metatarsal fractures followed by 63 cases of proximal phalanx fractures. Among the midfoot injuries, Lisfranc fracture dislocation was more common accounting for 12 out of 38 cases. Calcaneal fractures were more common among hindfoot injuries accounting for 27 out of 45 cases. Conclusions: To conclude, foot injuries account for 13.4% of all musculoskeletal injuries. 68.2% accounts for bony injuries. Among foot bony injuries, forefoot injuries (78.4%) are more common.